2020
DOI: 10.1097/md.0000000000021906
|View full text |Cite
|
Sign up to set email alerts
|

Treatment to reduce vascular calcification in hemodialysis patients using vitamin K (Trevasc-HDK)

Abstract: Introduction: End stage renal failure patients on hemodialysis have significant vascular calcification This is postulated to be related to sub-clinical vitamin K deficiency, which is prevalent in hemodialysis patients. Vitamin K deficiency result in the failure of the matrix GLA protein (MGP) to undergo carboxylation. MGP is a natural local inhibitor of vascular calcification and the lack of functional carboxylated MGP may contribute to increase vascular calcification. Vitamin K supplement should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…Because correcting vitamin K deficiency would particularly benefit CKD patients and because it is safe, 26 various randomized controlled trials have been performed or are ongoing to assess the effects of vitamin K supplementation on cardiovascular calcification and other morbidity in CKD patients. [27][28][29][30] Most of these trials employ dietary supplements of MK7, because long-chain menaquinones are believed to also act in nonhepatic tissues. In addition, among the vitamin K2 species, MK7 is readily available in synthetic form (albeit not drug grade) and exhibits a long half-life in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Because correcting vitamin K deficiency would particularly benefit CKD patients and because it is safe, 26 various randomized controlled trials have been performed or are ongoing to assess the effects of vitamin K supplementation on cardiovascular calcification and other morbidity in CKD patients. [27][28][29][30] Most of these trials employ dietary supplements of MK7, because long-chain menaquinones are believed to also act in nonhepatic tissues. In addition, among the vitamin K2 species, MK7 is readily available in synthetic form (albeit not drug grade) and exhibits a long half-life in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The CKD uniqueness is supported by the contrasting results of the AVC cohort, as well as other non-CDK cohorts, where vitamin K supplementation was capable of lowering dp-ucMGP levels even below levels observed in healthy controls and consequently attenuated progression of AVC [8,37]. Overall, research coverage on the effect of vitamin K supplementation in VC remains unsatisfactory, and several other studies are currently under way to build a stronger data foundation [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…159 A Singaporian ongoing trial also assesses the cardiovascular effects of MK7, 360 mg, given 3 times weekly for a total duration of 18 months to hemodialysis patients. 161 None of the above studies reported any adverse events related to vitamin K supplementation.…”
Section: Vitamin K Supplementationmentioning
confidence: 90%